Associations of common copy number variants in glutathione S‐transferase mu 1 and D‐dopachrome tautomerase‐like protein genes with risk of schizophrenia in a Japanese population. Issue 7 (14th July 2015) - Nakamura, Toru; Ohnuma, Tohru; Hanzawa, Ryo; Takebayashi, Yuto; Takeda, Mayu; Nishimon, Shohei; Sannohe, Takahiro; Katsuta, Narimasa; Higashiyama, Ryoko; Shibata, Nobuto; Arai, Heii
Abstract : Oxidative‐stress, genetic regions of interest (1p13 and 22q11), and common copy number variations (CNVs) may play roles in the pathophysiology of schizophrenia. In the present study, we confirmed associations between schizophrenia and the common CNVs in the glutathione (GSH)‐related genes GSTT1, DDTL, and GSTM1 using quantitative real‐time polymerase chain reaction analyses of 620 patients with schizophrenia and in 622 controls. No significant differences in GSTT1 copy number distributions were found between patient groups. However, frequencies of characterized CNVs and assumed gain alleles of DDTL and GSTM1 were significantly higher in patients with schizophrenia. In agreement with a previous report, the present data indicate that gains in the CNV alleles DDTL and GSTM1 are genetic risk factors in Japanese patients with schizophrenia, and suggest involvement of micro‐inflammation and oxidative stress in the pathophysiology of schizophrenia. © 2015 Wiley Periodicals, Inc.